Antimicrobial Resistance of Staphylococcus aureus and Coagulase‑negative Staphylococci from Bovine Mastitis Milk with Detection of Interleukins in Milk and Serum of Infected Cows - Shehab, Aya; Elkenany, Rasha; Younis, Gamal (Journal of Advanced Veterinary Research, 2023)
Staphylococci are the most typical bacteria found in cattle with mastitis, either Staphylococcus aureus or coagulase-negative Staphylococci (CNS). The studyâ€™s goal was to determine the prevalence of Staphylococci in bovine mastitis, the antimicrobial profile, and evaluate the concentration of pro-inflammatory interleukins (IL-4, IL-6, IL-10) related to the inflammatory response in clinical mastitis by ELISA. S. aureus (54%) and CNS (19%) were detected in 400 samples of milk from both clinical and subclinical bovine mastitis. The S. aureus isolates revealed higher resistance to ampicillin (100%), followed by amoxicillin-clavulanic acid (98.1%), cefotaxime (88.9%), erythromycin (63.2%), cefuroxime (63%), and tetracycline (61.1%). Furthermore, the CNS isolates showed high resistance against amoxicillin-clavulanic acid (100%), followed by ampicillin (94.7%), cefotaxime (89.5%), erythromycin (79.6%), cefuroxime (89.5%), and tetracycline (73.7%). However, the high susceptibility of S. aureus and CNS was observed to imipenem and ciprofloxacin. Furthermore, Cows with clinical mastitis reported high levels of IL-6 in both their serum and their milk. While they have much lower levels of IL-4 and IL-10 than normal ones (P < 0.001). In conclusion, it is recommended that laboratory results be carefully interpreted to avoid antimicrobial therapy for Staphylococci that is not clinically relevant and to ensure the advisable use of antimicrobials. Also, further study on the application of interleukins as therapeutic agents against bovine mastitis should be considered. Â